Applications in opto-electronics: general discussion - Backes, Claudia; Bartus, Szymon; Casiraghi, Cinzia; Ferrari, Andrea; Kamali, Ali Reza; Kolibal, Miroslav; Kumar, Vimal; Oyarzún Aravena, Andrea María; Oyarzun, Andrea; Palermo, Vincenzo; Sengupta, Amretashis; Silvestri, Alessandro; et al. (My University, 2021)
Alessandro Silvestri opened the discussion of the paper by Alessandro Molle: Can the encapsulation technique described in the paper affect the chemical-physical properties of the 2D material encapsulated? Could you comment regarding possible changes in the electron distribution and reactivity/i
Keywords: None